FOSSIL LAGOMORPHA (MAMMALIA) OF ITALY: SYSTEMATICS AND BIOCHRONOLOGY (Rivista italiana di Paleontologia e Stratigrafia, 2020)
Revisions performed in the last 15 years added remarkable novelties to the taxonomy and biochronology of Italian fossil lagomorphs. Several new taxa have been erected basing on new materials and on the revision of old materials. This paper aims to illustrate the state of the art of such researches. The lagomorph diversity in the Italian Neogene and Pleistocene is quite high, accounting 9 ochotonids, 14 leporids, and 3 stem lagomorphs. Among the lagomorph taxa recorded in Italy, quite a high number are insular or continental endemics. The oldest Italian lagomorphs are the insular endemic Paludotona aff. minor, P. etruria and P. minor from the early-middle Turolian of the Tusco-Sardinia palaeobioprovince, and Prolagus apricenicus and P. imperialis from the late Turolian of the Abruzzi-Apulia palaeobioprovince. In the Italian peninsula, lagomorphs are known since the late Turolian (early Messinian) [...]